Vascular anastomoses «suspended - Crestanello, Francisco; Carrera, Carlos; Sanguinetti, Julio; Corradi, Daniel; Vallverdú, Martín (Cirugía del Uruguay, 1991)
Authors present a technical modification for continuous suture vascular anastomosis, which they have systematical/y used for severa/ years. This modification is made possible by the great slipperiness of modern monofi/ament synthetic sutures. lt consists of the execution of the first half of the suture with separated vascular stumps under direct visual control of the lumen, the intima, and their edges. They are then brought into contact by making the thread slip with a slight traction. This makes possible the making of technically correct anastomosis quick/y and easi/y in difficult situations such as sma/1 vesse/s, deep ones, or those which cannot be dissecated extensive/y.